EKSTRAKSI LITIUM PADA AIR FORMASI PANAS BUMI DENGAN METODE ADSORPSI (STUDI KASUS PADA PLTP DIENG) - Ababil, Pijar Fitrah; Mahendra, Faroucki Seven; Faiqotul Hikmah; Lilo Al Fiqriansyah; Nanda Wulansari (Petroleum Engineering, Faculty of Engineering, University of Jember, 2023)
Geothermal energy is produced due to the tectonic and volcanic activity of a hydrothermal system in the earth. Geothermal potential in Indonesia is 28,170 MW, but only 1728 MW or 4% of the geothermal potential is utilized as a source of Geothermal Power Plant (GPP). The development of GPP requires a very large investment and is not comparable to the selling price of electricity. The principle of GPP is to use hot steam from the reservoir to generate electricity through a generator. The produced fluid consists of steam and brine water which will later be discharged/reinjected. Brine water comes from meteoric water that settles around the reservoir rocks. This precipitation process will dissolve minerals in the reservoir rock, one of which is lithium which is the raw material for batteries. There are various methods to extract lithium from brine water, including precipitation, ion-exchange, extraction with ion-in-liquids (ILs), and adsorption. The lithium extraction process begins with brine that is adsorbed using Li-ion-sieves and will be eluted with dilute HCl and then precipitated with Na2CO3 to become LiCO3 which will be marketed as battery raw material. The brine at Dieng GPP has a lithium content of 50.11 to 99.4 mg/L in the brine, if the flow rate is 70 tons/hour, 1.89 tons/month of LiCO3 will be obtained.